Communicating our research findings: Do we say what we mean and mean what we say? - Asraf, Ratnawati Mohd.; Brewer, James K. (Journal of Modern Languages, 2017)
In the field of linguistics and language teaching, the trend in research over the past 25 years has been toward the quantitative (Henning, 1986), which is commonly understood by researchers to be those studies that use statistics in the description and analysis of data. Indeed, not only are more quantitative studies being published in our journals, there is a distinct trend, according to Henning, toward greater use of inferential as opposed to descriptive statistics. Although Henning sees this as bringing language acquisition research into the realm of scientific inquiry, many have expressed concern regarding its misuse (Bakan, 1967; Brewer, 1991; 1996; Carver, 1978; Hays, 1994; Oakes, 1986; Shaver, 1993). Most of these concerns have to do with researchers' extrapolating their findings beyond what statistics can actually say, thereby having serious implications on the meaningfulness of their findings and on the validity of the conclusions reached.